(untitled) (Marketing Journal, 2025)
This article provides an in -depth analysis of the economic development level of small enterprises and microfirms in Uzbekistan based on statistical data and sample surveys. The study identifies the number, activity sectors, and economic conditions of small business entities across regions, and assesses the dynamics of business environment indicators. In particular, it examines trends in the self -assessment of small enterprisesʼ economic status, sectoral changes, and development prospects for the period 2018 –2023. The results serve as an important foundation for evaluating the 376 effectiveness of state policies aimed at small business development and for formulating practical recommendations.